AUTOMATIC DISTILLATION OF SALT GROUND WATER BECOME FEATURED FOR CONSUMPTION - Purnomo, Nopi; Andrianto, Richi (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: Salty groundwater is water that comes from the ground, has a high salt content and is unfit for consumption. The problem faced by the community is the difficulty of obtaining clean water which makes people buy clean water for their daily needs such as drinking, bathing, washing and so on. The community processing salty groundwater so that it can be drunk is still not efficient, because it is still done manually by cooking the salty groundwater using a pot and stove to produce water vapor, then it is collected using a glass or other container. The purpose of this research is to produce an automatic distillation device using an electric water heater to be able to detect water temperature, salt content, and water level with rocks using the Arduino Uno Microcontroller. The method used in this study uses data collection and system development (prototype) methods. The results of the research resulted in an automatic distillation device that can separate the salt content in salty groundwater so that the water is suitable for consumption and also produces salt that can be used by the community for household needs.            Keywords: distillation apparatus; microcontroller; prototype; salty groundwater  Abstrak: Air tanah asin merupakan air yang berasal dari dalam tanah, memiliki kadar garam yang tinggi dan tidak layak untuk dikonsumsi. Masalah yang dihadapi masyarakat adalah kesulitan akan air bersih membuat masyarakat membeli air bersih untuk kebutuhan sehari-hari seperti minum, mandi, mencuci dan lain sebagainya. Masyarakat mengolah air tanah asin agar dapat diminum masih belum efisien, karena masih dilakukan secara manual dengan memasak air tanah asin menggunakan panci dan kompor untuk menghasilkan uapan air, kemudian ditampung menggunakan gelas atau wadah lainnya. Tujuan penelitian ini menghasilkan suatu alat destilasi otomatis menggunakan pemanas air listrik untuk dapat mendeteksi suhu air, kadar garam, dan level ketinggian air dengan batuan menggunakan Mikrokontroler Arduino Uno. Metode yang digunakan dalam penelitian ini menggunakan metode pengumpulan data  dan pengembangan sistem (prototype). Hasil penelitian menghasilkan suatu alat destilasi otomatis yang dapat memisahkan kadar garam pada air tanah asin sehingga air tersebut layak dikonsumsi dan juga menghasilkan garam yang dapat dimanfaatkan masyarakat untuk keperluan dalam rumah tangga. Kata kunci: air tanah asin; alat destilasi; mikrokontroler; prototype